ANALISIS PRODUKTIVITAS PARSIAL DEPARTEMEN PRODUKSI DENGAN METODE OMAX DI PT GANDUM MAS KENCANA - Aluwi Aluwi (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: This thesis discusses the analysis of production department partial productivity measurement with the method of Objective Matrix (OMAX) in Building G-line PT Gandum Mas Kencana. Objective methods of Matrix (OMAX is a partial productivity measuring system to monitor productivity according to the existence of the object or part. In the method of OMAX criteria – the criteria or key performance indicator (KPI) that affect the productivity index was defined clearly and must be donefor each weighting criteria. In their weighting criteria, the method used is the Analytical Hierarchy Process (AHP). Object of research was done on the line of Buildings G PT Gandum Mas Kencana that producing compound chocolate. Criteria – the criteria that influence the productivity of the line of building G, namely: a raw material partial productivity, the productivity of the workforce, the effectiveness of electricity power, overtime working hours minimize, minimize labor costs, downtime minimize, productdefects minimize and semi-finished products minimize. Determination of standard performance done on the second semester in 2012, then the causal analysis is performed by using fishbone diagrams to find the causes of the low productivity of the line of G Building. Results of the analysis and proposal of improvement, then the average productivity index in the January to August 2013 in line G Building increased.Keywords: Objective Matrix (OMAX), Analytical Hierarchy Process (AHP),Productivity Index.